2020
DOI: 10.1038/s41467-019-14050-z
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity and clonal evolution in liver cancer

Abstract: Clonal evolution of a tumor ecosystem depends on different selection pressures that are principally immune and treatment mediated. We integrate RNA-seq, DNA sequencing, TCRseq and SNP array data across multiple regions of liver cancer specimens to map spatio-temporal interactions between cancer and immune cells. We investigate how these interactions reflect intra-tumor heterogeneity (ITH) by correlating regional neo-epitope and viral antigen burden with the regional adaptive immune response. Regional expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
237
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(266 citation statements)
references
References 77 publications
(82 reference statements)
6
237
0
Order By: Relevance
“…219 Notably, antitumor immune responses have also been proven to exhibit spatial heterogeneity. 220,221 Reuben et al observed extensive spatial differences in T-cell density and clonality in distinct regions of the same tumors, suggesting substantial intratumoral heterogeneity of the T-cell repertoire. 222 Consistently, Losic et al demonstrated spatial cancer-immune interactions and found that tumor-associated immune infiltrates exhibited regional heterogeneity with distinct tumor regions showing different levels of immune clonal expansion and antigen-specific T-cell responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…219 Notably, antitumor immune responses have also been proven to exhibit spatial heterogeneity. 220,221 Reuben et al observed extensive spatial differences in T-cell density and clonality in distinct regions of the same tumors, suggesting substantial intratumoral heterogeneity of the T-cell repertoire. 222 Consistently, Losic et al demonstrated spatial cancer-immune interactions and found that tumor-associated immune infiltrates exhibited regional heterogeneity with distinct tumor regions showing different levels of immune clonal expansion and antigen-specific T-cell responses.…”
Section: Resultsmentioning
confidence: 99%
“…222 Consistently, Losic et al demonstrated spatial cancer-immune interactions and found that tumor-associated immune infiltrates exhibited regional heterogeneity with distinct tumor regions showing different levels of immune clonal expansion and antigen-specific T-cell responses. 221 The spatial heterogeneity of antitumor immunity may correlate with the intratumoral heterogeneity of cancer cells. Cancer cells are commonly composed of different subclones located in distinct compartmentalized regions that harbor distinct genomic, phenotypic, and antigenic diversities.…”
Section: Resultsmentioning
confidence: 99%
“…Recent multiomic analyses have explored and described intensive ITH in TME of HCC 10 . Other recent studies using immunogenomics approach addressed how the immune landscape contributes to genomic-ITH in ovarian cancer 11 and HCC 12 . Despite that, ITH on the immune landscape remains a correlative feature associated with tumour genomic-ITH and its direct clinical impact and role in tumour evolution unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity is another major characteristic of cancer [11]. It promotes cancer resistance to therapy and even retards immunotherapy responses [53]. Heterogeneity indicates that various types of cells are present in an individual tumor, while a specific signal may play a predominant role in different cells and in different stages of cancer [11,[54][55][56][57][58].…”
Section: Copy Number Alterations Of Target Genes and Activation Of Bymentioning
confidence: 99%